Constructing Childhood Realities: A Communication Science Analysis of TikTok’s Age Verification Failure and Psychosocial Impact - HF, Nurul Hasriani; An Nur, Fitrinandan (LEGAL BRIEF, 2025)
This study explores the failure of TikTok’s age verification system and its psychosocial impact on children aged 10 to 13 in Indonesia. Although the platform sets official age restrictions, many minors are able to bypass these controls and gain access to content that is not suitable for their developmental stage. The analysis highlights how this exposure can lead to increased anxiety, social pressure, distorted self-image, and reduced emotional well-being. The research identifies several contributing conditions in Indonesia, such as the large number of young users, high daily engagement, gaps in regulatory enforcement, cultural practices that increase minors’ visibility online, and recurring technical issues in the verification process. Content analysis revealed common themes in accessible material, including suggestive behavior, mild violence, commercialized influencer culture, and unrealistic body ideals. These patterns suggest that prolonged and repeated exposure shapes children’s perceptions of social norms and expectations, influencing their self-concept and interactions with peers. The findings underscore the urgent need for stronger collaboration between government authorities, digital platforms, and parents. This includes improving verification mechanisms, strengthening regulatory measures, and integrating digital literacy education from an early age to build resilience and equip children with the skills needed to navigate the digital environment safely.